Innovative strategies in genitourinary cancer: the role of oncolytic viruses - Zhang, Jie; Liu, Kepu; Zhu, Zheng; Shang, Shihao; Wei, Di; Zheng, Yu; Zhang, Lei; Liang, Ying; Ju, Dongen; Yuan, Jianlin (Frontiers in Oncology, 2024)
Urinary tumors pose a significant health threat because of their high prevalence and recurrence rates. Despite the availability of various treatment options, many patients poorly respond to traditional therapies, highlighting the urgent need for alternative approaches. Oncolytic viruses are promising therapeutic agents. These viruses exploit the unique characteristics of cancer cells to specifically target and destroy them, thereby triggering potent antitumor immune responses. This review delves into recent advancements and future prospects of oncolytic viruses, focusing on their application in renal, bladder, and prostate cancers. By discussing practical implications and the potential of different viruses, including the cowpox virus, adenovirus, measles virus, coxsackievirus, and reovirus, we pave the way for further exploration and refinement of this exciting field.